Development of Education Policy in Indonesia - Hariyono, Eko; Maisyaroh, Maisyaroh (Universitas Negeri Malang, 2024)
Curriculum policies in Indonesia have undergone changes since the pre-independence period until now. This study aims to analyze policy developments in Indonesia so that it can provide an overview of the mapping of the themes that have been researched, the mapping methodology used in the article, and the year of publication of the article. The method used in this study is Systematic Literature Review (SLR) by using the keyword education policy in Indonesia on the Google Scholar engine using Indonesian, the articles searched are limited to 2015 to 2023. The results of the study found several themes, namely, education policy on the curriculum and the impact of education policy on learning in Indonesia, the research method used in the analyzed articles was 9 articles in the qualitative motode and 1 article in the development method, then the analyzed articles were articles in 2015, 2016, 2019 as many as 1 article each, while in 2021, 2022 2 each, and 2023 3 articles. Thus, it can be concluded that education policy in Indonesia has experienced significant development and has an impact on learning.